Inklusifitas Hukum Islam ‎(Ayat-ayat Hukum Bisnis dalam al-Qur’an)‎ - suqiyah musafa'ah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2008)
Islamic law is deduced from the Qur’anic verses and the practices of the prophet Muhammad SAAS, during his period in Mecca as well as in Medina. Laws and rules scattered in the Qur’an is those for all humanity regardless their religious conviction. Thus, when the Prophet was successful in establishing an Islamic state in Media, the Qur’an relentlessly stressed the inclusiveness of its law and regulation to whoever needs it, be he or she a Muslim or otherwise. This inclusiveness is also shown on those verses from Mecca as well as Medina period about commercial transactions and business activities. Those rules and laws are not intended only for Muslims but for whoever parties involve in such activities. Therefore, those rules are open for any party willing to uphold principles of justice, mutual guarantee, and benefit. This inclusiveness of rules and law of business in the Qur’an and their implementation are the main focus of this article.